Transcriptome Responses of Ripe Cherry Tomato Fruit Exposed to Chilling and Rewarming Identify Reversible and Irreversible Gene Expression Changes - Hunter, Donald A.; Napier, Nathanael J.; Erridge, Zoe A.; Saei, Ali; Chen, Ronan K. Y.; McKenzie, Marian J.; O’Donoghue, Erin M.; Hunt, Martin; Favre, Laurie; Lill, Ross E.; Brummell, David A. (Frontiers in Plant Science, 2021)
Tomato fruit stored below 12 oC lose quality and can develop chilling injury, particularly upon subsequent transfer to a shelf temperature of 20 oC. The more severe symptoms of altered fruit softening, uneven ripening and susceptibility to rots can cause postharvest losses. In this study, we compared the effects of exposure to mild (10 oC) and severe chilling (4 oC) storage temperatures on the fruit quality and transcriptome of ‘Angelle’, a cherry-type tomato, harvested at the red ripe stage. Storage at 4 oC for 27 d plus an additional 6 d at 20 oC caused accelerated softening and the development of mealiness, both of which are usually related to cell wall metabolism. Transcriptome analysis using RNA-Seq identified a range of transcripts encoding enzymes putatively involved in cell wall disassembly whose expression was strongly down-regulated at 4 oC, suggesting that accelerated softening was due to reductions in turgor rather than to increased cell wall disassembly. Transcript abundances of these genes were also suppressed at 10 oC, and most were only partially restored upon transfer of the fruit from 4 to 20 oC. Within 1 d of exposure to 4 oC, large increases occurred in the expression of alternative oxidase, superoxide dismutase and several glutathione S-transferases, encoding enzymes that protect cell contents from oxidative damage. Numerous heat shock proteins and chaperonins also showed large increases in expression, with genes showing peak transcript accumulation after different times of chilling exposure. These changes in transcript abundance were not induced at 10 oC, and were reversible upon transfer of the fruit from 4 to 20 oC. Pathways involved in ribosome biogenesis and protein degradation were enhanced at 4 oC, perhaps to repair chilling damage. We also identified several transcripts that showed very large fold increases upon exposure to chilling conditions. These highly temperature-responsive transcripts could be useful molecular markers of cold response.